A systematic review of sexual and reproductive health interventions for young people in humanitarian and lower-and-middle-income country settings - Desrosiers, Alethea; Betancourt, Theresa; Kergoat, Yasmine; Servilli, Chiara; Say, Lale; Kobeissi, Loulou (BMC public health, 2020)
Background Accessibility of sexual and reproductive health (SRH) services in many lower-and-middle-income countries (LMICs) and humanitarian settings remains limited, particularly for young people. Young people facing humanitarian crises are also at higher risk for mental health problems, which can further exacerbate poor SRH outcomes. This review aimed to explore, describe and evaluate SRH interventions for young people in LMIC and humanitarian settings to better understand both SRH and psychosocial components of interventions that demonstrate effectiveness for improving SRH outcomes. Methods We conducted a systematic review of studies examining interventions to improve SRH in young people in LMIC and humanitarian settings following Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) standards for systematic reviews. Peer-reviewed journals and grey literature from January 1, 2000 to December 31, 2018 were included. Two authors performed title, abstract and full-text screening independently. Data was extracted and analyzed using a narrative synthesis approach and the practice-wise clinical coding system. Results The search yielded 813 results, of which 55 met inclusion criteria for full-text screening and thematic analysis. Primary SRH outcomes of effective interventions included: contraception and condom use skills, HIV/STI prevention/education, SRH knowledge/education, gender-based violence education and sexual self-efficacy. Common psychosocial intervention components included: assertiveness training, communication skills, and problem-solving. Conclusions Findings suggest that several evidence-based SRH interventions may be effective for young people in humanitarian and LMIC settings. Studies that use double blind designs, include fidelity monitoring, and focus on implementation and sustainability are needed to further contribute to this evidence-base.